Phased, chromosome-scale genome assemblies of tetraploid potato reveals a complex genome, transcriptome, and predicted proteome landscape underpinning genetic diversity - Hoopes, G.; Meng, X.; Hamilton, J.P.; Achakkagari, S.R.; Brito Ribeiro, Mauro César Lambert de; Bolger, M.E.; Coombs, J.J.; Esselink, D.; Kaiser, N.R.; Kodde, L.; Kyriakidou, M.; Lavrijssen, B.; et al. (Elsevier, 2022)
Cultivated potato is a clonally propagated autotetraploid species with a highly heterogeneous genome. Phased assemblies of six cultivars including two chromosome-scale phased genome assemblies revealed extensive allelic diversity including altered coding and transcript sequences, preferential allele expression, and structural variation that collectively result in a highly complex transcriptome and predicted proteome which are distributed across the homologous chromosomes. Wild species contribute to the extensive allelic diversity in tetraploid cultivars, demonstrating ancestral introgressions predating modern breeding efforts. As a clonally propagated autotetraploid that undergoes limited meiosis, dysfunctional and deleterious alleles are not purged in tetraploid potato. Nearly a quarter of the loci bore mutations predicted to have a high negative impact on protein function, complicating breeder’s efforts to reduce genetic load. The StCDF1 locus controls maturity and analysis of six tetraploid genomes revealed 12 allelic variants correlated with maturity in a dosage dependent manner. Knowledge of the complexity of the tetraploid potato genome with its rampant structural variation and embedded deleterious and dysfunctional alleles will be key not only to implementing precision breeding of tetraploid cultivars but also to the construction of homozygous, diploid potato germplasm containing favorable alleles to capitalize on heterosis in F1 hybrids.